DETERMINAN KUNJUNGAN ANTENATAL CARE DI AREA PEDESAAN INDONESIA (Analisis Data Riskesdas 2013) - Elsi Arisanti; M. Hakimi; Mubasysyir Hasanbasri (Departemen Kebijakan dan Manajemen Kesehatan, Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2016)
Background: AKI is an indicator to determine the health statusin a country. The maternal mortality ratio in Indonesia was228/100.000 live births in 2008 to 220/100.000 live births in2010 and there was an increase to 359/100.000 live births in2013, while the MDGs target for 2015 was 102 per 100.000 livebirths. In Indonesia, the main causes of maternal death arebleeding, hypertension and infection. Antenatal care has beenproven effective in early detection of conditions that causematernal death. social approaches also need to be consideredas indirect causes such as socio-demographic factors,unavailability of birth attendants, costs. In public healthsciences, the social approach is a social determinant of health.The use of Antenatal Care is not optimal due to the limitedsupport of the health system and the influence of socioeconomicconditions and the rural environment.Purpose: To identify determinants of antenatal care visits inrural areas in Indonesia based on data analysis of Riskesdas2013.Methods: This type of research is quantitative using data fromthe 2013 Basic Health Research. Respondents in this studywere mothers who had been pregnant and gave birth during theperiod of January 1st 2010 to 2013 aged 10-59 years and live inrural Indonesia Results: After a statistical test was carried out, the antenatalcare visits in rural Indonesia were 90.41%. The factors that mostinfluenced antenatal care visits in rural areas were informationon knowledge of the availability of midwives for practice (Pvalue= 0.001, OR = 2.01) and information on knowledge of theavailability of posyandu (P-value = 0.001, OR = 1.93). Conclusion: Antenatal care visits in rural Indonesia are stillquite high. There is a relationship between individual factors andhealth system factors on antenatal care visits in rural areas.Individual factors cannot stand alone without health systemfactors. Health system factors are more important thanindividual factors. There needs to be an increase in the qualityand quantity of information for health cadres and the communityabout the importance of antenatal care visits.